How do Brazilian National Park managers evaluate the relationship between conservation and public use?. Issue 131 (May 2022) - de Omena, Michel Tadeu Rodrigues Nolasco; Hanazaki, Natalia
Abstract: Protected areas, such as national parks, are among the most widespread nature conservation strategies in the world. This study used online forms to consult Brazilian national park managers in all biomes about the relationship between park conservation and public use variables. Then, based on suggested public use and conservation variables, we analysed how the managers viewed this relationship. Our findings indicate that the most important conservation status assessment variables are considered to be the presence of endangered species, the percentage of regularised park area, the number of employees and the number of employees relative to the protected area. The variables considered to be least relevant are park age, park area, management plan age and management report results. Ninety-seven per cent of the participants identified a relationship between conservation and public use, which was particularly expressed by the number of ecosystem services provided by the park, the number of research studies into endangered species associated with the park and the diversity of research project knowledge areas. Improving tools for obtaining park conservation status compatible with managers' perceptions is highly important for park management to facilitate planning and optimising activities that foster conservation. Highlights: What are the best variables for calculating conservation status in Brazilian Parks? Managers' perception contribute to know which variables are related to conservation. Endangered sp and land tenure regularisation are the best conservation indicators. SAMGe report has the best matches in the perception of Brazilian Parks managers. Good management of public use is important for the conservation of protected areas.